Peningkatan Kompetensi Guru TK Aisyiyah dalam Menanamkan Nilai Al-Islam Kemuhammadiyahan kepada Anak Usia Dini - Intisari (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service program aims to enhance teachers’ competencies in understanding and implementing Al-Islam and Muhammadiyah values in Early Childhood Education learning at TK Aisyiyah, to develop learning materials integrated with character values, and to strengthen an Islamic school culture through habituation and role modeling. The main problem faced was the limited ability of teachers to integratively and practically incorporate Islamic values into play activities and daily learning processes. The methods employed included participatory training, interactive workshops, microteaching sessions, and direct classroom mentoring, implemented through stages of preparation, execution, implementation, product development, evaluation, and dissemination. Evaluation was conducted through pre-tests and post-tests, classroom observations, and assessments of the learning tools produced. The results of the program indicated a significant improvement in teachers’ knowledge, with an average increase of 40 percent, enhanced value-based teaching implementation skills among 85 percent of the teachers, and the development of learning tools in the form of character-based Daily Lesson Plans, Islamic learning media, and daily habituation guidelines. The program achievement level was categorized as high, with accomplishments ranging from 85 to 100 percent across most indicators. This program had a positive impact on improving teachers’ consistency in serving as role models, strengthening a school culture grounded in Islamic values, and creating a learning environment that supports the development of moral character and positive behavior in early childhood learners. These findings demonstrate that systematic training and mentoring are effective in strengthening the internalization of Al-Islam and Muhammadiyah values within the Early Childhood Education environment.